The Voice of the Bridegroom in John 3:29 and in the Context of Jewish and Christian Literature - Blumhofer, Christopher (Bulletin for biblical research, 2024)
This article examines John the Baptist’s reference to "the voice of the bridegroom" in John 3:29. The primary context in which this expression should be heard is that of the Old Testament expectation that the time of eschatological redemption will be marked by the renewed sound of "the voice of the bride and the voice of the bridegroom" within Israel (Jer 33:11). Interpretations that emphasize sociocultural or spiritual understandings of this phrase should be considered secondary to this primary frame of reference. The intertextual interpretation links the text to the broader narrative tendencies of the Fourth Gospel, to late first-century Judaism, and to Jewish liturgy from late antiquity to the modern period.